Gangguan Muskuloskeletal Terkait Pekerjaan (WMSD) dan Produktivitas Kerja di Kalangan Karyawan Universitas: Sebuah Studi Eksploratif Lintas Sektoral - Dela Fariha Fuadi; Andrew Wijaya Saputra; Cicilia Febriani Hayuningrum; Nesi Nesi; Putri Karina Syafitri (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Work-related musculoskeletal disorders (WMSDs) are highly prevalent among office workers and have been associated with reduced work productivity. However, evidence examining both ergonomic risk and work productivity simultaneously among university employees remains limited, especially in developing countries. This study aimed to identify potential risk factors for WMSDs and examine their association with work productivity among university employees. Materials and methods. This exploratory cross-sectional study involved 30 university employees selected through purposive sampling. WMSDs were assessed using the Nordic Body Map (NBM), and productivity (including absenteeism and presenteeism) was measured with the World Health Organization-Health and Work Performance Questionnaire (HPQ). Ergonomic risk was evaluated using the Rapid Office Strain Assessment (ROSA). Data were analyzed with descriptive statistics, as well as Fisher’s Exact and Mann-Whitney U tests (p<0.05). Results. The most common WMSDs were low back pain (LBP) (70%), upper neck pain (UNP) (66.7%), and right shoulder pain (RSP) (53.3%). Ergonomic risk was significantly associated with LBP (p=0.021). UNP was associated with lower work performance (p=0.038) and increased absenteeism (p=0.013), while LBP was also associated with higher absenteeism (p=0.037). Conclusions. These findings suggest that WMSDs, particularly in the neck and lower back, are associated with reduced work productivity. Improving workplace ergonomics may help reduce these issues and enhance work performance.